Online stakeholder relationship strategies on Facebook used by South African universities - Sabryna Joanne Tsinga Mambadja; David Pieter Conradie; De la Rey Van der Waldt (Communicare)
The use of social networking sites is becoming increasingly essential to communicate and establish long-term relationships with stakeholders. In order for universities to retain their stakeholders, the effective use of media like Facebook is evident. This study investigated the Facebook pages of 24 South African universities by means of a content analysis, to determine how they have structured and populated their Facebook pages with different types of content that could be relevant to their public relations communication strategies. The theoretical basis of the content analysis consisted of the three virtual communication strategies developed by Waters et al. (2009), namely disclosure, information dissemination and involvement. This study came to the general conclusion that South African universities had not yet capitalised on Facebook to fully integrate the three virtual communication strategies in order to enhance online stakeholder relationships.